(untitled) (Damascus University Journal for engineering sciences, 2022)
The performance of the buildings is defined by the least electrical consumption and by utilizing the natural resources. Utilizing the daylight affects the electrical lighting consumption. There are some factors that contribute in increasing the utilizing the daylight. In this article, directing the office, the Window to Wall Ratio WWR%, Visible Light Transmittance ratio VLT%, and wall reflecting ratio are studied to define their effects on utilizing the daylight and on decreasing the electrical lighting consumption. This is done according to the geographic location of Syria and based on international standards which define the utilizing conditions of daylight. The study is carried out via DIVA which is a plug-in to Rhino which is a 3D simulation software. This study provided guideline values that aid to design offices in order to utilize daylight and to decrease the electrical lighting consumption.